Late-Holocene fire history in a forest-grassland mosaic in southern Brasil: Implications for conservation - Behling, Hermann; Pillar, Valério D.; Müller, Sandra C.; Overbeck, Gerhard E. (Applied vegetation science, 2007)
Question: Is the diverse mosaic of forest/grassland (Campos) vegetation on the hills in the Porto Alegre region natural or of anthropogenic origin? What are the best approaches to management and conservation of forest/grassland mosaics in southern Brazil? Location: 280 m a.s.l., Rio Grande do Sul State (30°04′32″S; 51°06′05″W, southern Brazil. Methods: A 50-cm long radiocarbon dated sediment core from a swamp on Morro Santana was analysed for pollen and charcoal, and multivariate data analysis was used to reconstruct past vegetation and fire dynamics. Results: The formation of swamp deposits is related to a change to wetter climatic conditions since 1230 cal yr BP. The diverse forest/grassland mosaic existed already at that time and can be seen as natural in origin as it has been also shown from other studies in southern Brazil. Since 580 cal yr BP, forests expanded continuously. The marked higher occurrence of the pioneer Myrsine during the last 70 years, indicates a change in the disturbance regime. In the past, vegetation has been influenced by mostly anthropogenic fire, set first by Amerindians and later by European settlers. Conclusions: Management for conservation of forest/grassland mosaics should take into account, first, that grasslands are remnants of earlier drier Holocene periods and not a result of deforestation and, second, the history of disturbance by grazing and fire. Suppression of grazing and burning has likely resulted in a trend towards more woody vegetation under modern wet climatic conditions. If management for conservation excludes fire, the present grassland patches will tend to disappear due to forest expansion under the modern humid climate. Maintaining or reintroducing cattle grazing in conservation areas could be an alternative to fire. Abbreviations AD = Anno Domini; AMS = Accelerator mass spectrometry; Cal yr BP = calibrated years before 1950; PCoA= Principal Coordinates Analysis